Estudo teórico-experimental de ligação viga-pilar com consolo metálico embutido em estruturas pré-moldadas de concreto - Bachega, Luís Augusto (Universidade Federal de São Carlos, 2013)
This study aimed to analyze the structural behavior of a beam-column connection with embedded steel member for precast concrete with no current use still in Brazil. Based on the literature review about hidden corbels found in international technical references, a type of hidden corbel with embedded steel section (so called billet) was selected for this research. Although there are many different analytical models for the design of the billet within the available technical literature, the focus of this research was on the revised models found in the most recent design manuals PCI (2010) and FIB (2011). In addition to the analytical study an experimental investigation was conducted, wherein isolated column members with billet corbels were tested primarily to a full scale test of a sub-frame with two beams six meters long and with a central column assembled in cruciform shape. For the isolated model, named PI Model (Isolated steel corbel), the behavior of the steel corbel and its interaction with the column were evaluated. For the full scale test, named LI Model (connection zone model), the behavior of the connection zone and the behavior of the beam were studied interacting together. For both the theoretical and the experimental studies, the selected billet consisted of a rectangular hollow section of 200 mm x 100 mm x 10 mm in height, width and thickness, respectively. For the PI Model test, the billet showed a rigid behavior and it was capable of resist an applied load of 700 kN with no damage within the concrete of the column. For the case of LI Model, the experimental study analyzed the behavior of the whole connection zone, comprising both the steel corbel and the end of the beam near the corbel. For this case, the connection behaved as rigid until the applied shear force at the connection reached between 239,5 kN and 238,3 kN, for which the flexural stiffness of the connection acted as rigid, with fixity factors of 1.0 and 0.96, for the left and right connections, respectively. The failure of the model occurred at the cast in place topping of the composite beam when the shear force reached 473.5 kN. The comparison between the experimental results with the theoretical values demonstrated that the isolate billet showed compatible resistance with the expected but that the region of the beam top end showed premature failure due to lack of reinforcement in the region of the end of the beam. It is believed that this effect occurred because of the fact that the detailing followed from studies conducted in the UK is suitable for hinged connections while the connection analyzed in this research comprised of continuous negative reinforcing bars passing through the columns within the cast in place topping of the composite precast beam. Finally, this study presents further recommendations for improvements of the reinforcement detailing of the precast beam.
Estudo Teórico-Experimental de Ligação Viga-Pilar com Consolo Metálico Embutido em Estruturas Pré-Moldadas de Concreto
Keywords: Concreto pré-moldado; Ligações viga-pilar; Consolo metálico embutido; Beam-column connection; Hidden steel corbel; Precast structures; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL